2013
DOI: 10.1016/j.schres.2012.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and visual–spatial memory impairment in youth at familial risk for schizophrenia or affective psychosis: A pilot study

Abstract: Background Schizophrenia and affective psychoses share several common biological origins, particularly genetic susceptibility. Kraepelin posited that differing clinical expressions in these disorders reflect different etiopathologies. We tested a neuropsychological component of this hypothesis by evaluating verbal and visual memory performance in nonpsychotic youth at familial risk for psychosis, taking into account contributions to memory dysfunction including executive processing and psychopathology. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
1
9
0
2
Order By: Relevance
“…Similar results were found on measurements of verbal and linguistic abilities, specifically on the Word-Pair Test, where the FHR-SCZ group performed worse than the FHR-AFF group in immediate recall and 1-hr delayed recall Schubert & McNeil, 2005. However, in a study of verbal and visual memory using the identical sample as reported here, Scala et al (2013) reported no significant differences in verbal or spatial memory performance between the two groups of relatives. In Eastern Quebec Multigenerational Families, Maziade et al (2009) found that both relatives of schizophrenia and bipolar probands shared cognitive impairments in memory and executive functions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results were found on measurements of verbal and linguistic abilities, specifically on the Word-Pair Test, where the FHR-SCZ group performed worse than the FHR-AFF group in immediate recall and 1-hr delayed recall Schubert & McNeil, 2005. However, in a study of verbal and visual memory using the identical sample as reported here, Scala et al (2013) reported no significant differences in verbal or spatial memory performance between the two groups of relatives. In Eastern Quebec Multigenerational Families, Maziade et al (2009) found that both relatives of schizophrenia and bipolar probands shared cognitive impairments in memory and executive functions.…”
Section: Discussionsupporting
confidence: 84%
“…Participants are asked, "how much that problem has bothered you during the past 7 days including today"; thus, it is a measure of current symptomatology. In a previous report on this sample (Scala et al, 2013; Table 3), we reported that three SCL-90-R dimensions were significantly worse in the high-risk groups than in controls, Obsessive-Compulsive (FHR-AFF > controls), Phobic Anxiety (FHR-AFF > controls), and Psychoticism (FHR-SZ > controls), while none of the clinical scales significantly distinguished the two high-risk groups from each other. In this study, we tested the effects of these three variables as well as Depression on cognition, as depression is often associated with cognitive impairment.…”
Section: Measures Of Current Psychopathologymentioning
confidence: 59%
See 1 more Smart Citation
“…Abuse and neglect are known to have a negative influence on cognitive functioning in community samples of healthy adults 20,21 and children/adolescents 22,23 as well as in patients with psychosis. 8,24,25 Congruent with other studies, [26][27][28] we have reported that children from densely affected multigenerational families who had a parent affected by schizophrenia or BD had fullscale IQ impairments as well as deficits in specific cognitive domains, such as visual and verbal episodic memory, working memory and executive functions of initiation. 12,16 These domains are among the most impaired in adult patients and are consistently found to be associated with schizophrenia and BD.…”
Section: Introductionmentioning
confidence: 51%
“…While a variety of neuropsychological measures have been previously reported from the Harvard Adolescent FHR study (Seidman et al, 2006a,b;Scala et al, 2013), the line-drawing task data has not been previously reported. The FHR group consisted of the children (n = 14) and siblings (n = 19) of 25 adult probands who met DSM-IV criteria for SZ.…”
Section: Participantsmentioning
confidence: 99%